New Islamic Governance: The PAS and PKS Evolution - WELSH, Bridget (Institutional Knowledge at Singapore Management University, 2011)
Islamic political parties are often touted for their religious ideals, seen as providing religious comfort rather than economic and other social deliverables. Voters are seen to make a trade-off between a “good” government based on values rather than “good” government based on performance. Islamic parties in Malaysia and Indonesia – namely Parti Islam Se-Malaysia (PAS) and Parti Keadilan Sejahtura (PKS) – would ardently disagree with this stark choice. They contend that they are offering both values and governance. What then are the deliverables of these parties? How do they actually implement their style of government in practice? What are the underlying ideas and practices of “Islamic welfare”? How should the economy work? What ideas should be part of social welfare? The experience in both countries shows that PAS and PKS are transforming their ideas on how to govern, drawing from a robust discussion and practical experience of Islamic parties in office. This paper traces some of the recent ideas on how to govern “Islamically” in multi-national countries. Drawing from interviews of PAS and PKS leaders, with a focus on a handful of case studies of where these parties are in government at the local and state levels, this paper argues that a new formula of “Islamic governance” is evolving based on an embrace of the market, need-based and religious-education focused social welfare, and policy implementation led by professionals rather than uLAMa. The pattern of Islamic governance in practice offers greater prospects for inclusiveness and concrete deliverables than earlier experiences and policy articulations of these parties.